Extreme root resorption associated with induced tooth movement: A protocol for clinical management - Alberto Consolaro; Laurindo Zanco Furquim (Dental Press Editora, 2014)
Cases in which teeth have only the cervical third remaining from orthodontically induced external root resorption, cast the following doubts: 1) What care should be taken to keep these teeth in mouth with the least risk possible? 2) What care should be taken with regards to reading of imaging exams, particularly in terms of accurately determining cervical root and bone loss? 3) Why is not endodontic treatment recommended in these cases? The present study aims at shedding light on the aforementioned topics so as to induce new insights into the theme.